2018
DOI: 10.1186/s41021-018-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

Ozone augments interleukin-8 production induced by ambient particulate matter

Abstract: BackgroundExperimental and controlled human exposure studies have demonstrated additive effects of ambient particulate matter and ozone on health. A few epidemiological studies have suggested that ambient particulate matter components are important for the combined effects of ambient particulate matter and ozone on health. However, few studies have examined whether ozone changes the effects of ambient particulate matter on pro-inflammatory cytokine production. In this study, the influence of ozone on pro-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Also, a high correlation between nitrogen dioxide (NO 2 ) and particulate in inducing IL-6 hyperexpression was found (Perret et al, 2017), being both responsible of an inflammatory status even in a pediatric population (Gruzieva et al, 2017). Among the other more common pollutants, ozone (O 3 ) and sulfur dioxide (SO 2 ) have also a prominent role in inducing systemic and respiratory system inflammation, particularly via IL-8 (Kurai et al, 2018), IL-17 (Che et al, 2016) and TNF-a (Cho et al, 2007), both in vitro and in vivo (Knorst et al, 1996). All these modifications are well known to contribute to atherogenesis, chronic respiratory diseases and cardiovascular events, the latter strictly correlated with IL-6 serum levels (Aromolaran et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a high correlation between nitrogen dioxide (NO 2 ) and particulate in inducing IL-6 hyperexpression was found (Perret et al, 2017), being both responsible of an inflammatory status even in a pediatric population (Gruzieva et al, 2017). Among the other more common pollutants, ozone (O 3 ) and sulfur dioxide (SO 2 ) have also a prominent role in inducing systemic and respiratory system inflammation, particularly via IL-8 (Kurai et al, 2018), IL-17 (Che et al, 2016) and TNF-a (Cho et al, 2007), both in vitro and in vivo (Knorst et al, 1996). All these modifications are well known to contribute to atherogenesis, chronic respiratory diseases and cardiovascular events, the latter strictly correlated with IL-6 serum levels (Aromolaran et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is scientific evidence that exposes a high correlation between the presence of ozone (O 3 ), sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ) and fine particles in the induction of hyperexpression of proinflammatory interleukins ( Kurai et al., 2018 ; Perret et al., 2017 ). NO 2 is a common marker of air pollution/industrial activity, associated with morbidity and mortality ( He et al., 2020 ).…”
Section: Environmental Factors and Their Influence On Covid-19 Infectmentioning
confidence: 99%
“…IL-8 is normally secreted by normal cells in very small amounts, whose production and secretion increases following the increased levels of other pro-inflammatory cytokines such as IL-1 and tumor necrosis factor (TNF), bacterial and viral products, and cellular stress (Kurai et al, 2018). Previous studies conducted on the association among serum, intracellular, and extracellular levels of this factor showed that the IL-8 level significantly increases in the presence of malignancies such as melanoma, breast carcinoma, ovarian malignancies, and pancreatic cancer (Green et al, 1996;Chen et al, 2014;Chia et al, 2014;Yung et al, 2018).…”
Section: Ethical Approvalmentioning
confidence: 99%